In vivo mouse myocardial 31P MRS using three‐dimensional image‐selected in vivo spectroscopy (3D ISIS): technical considerations and biochemical validations. (13th August 2015) - Bakermans, Adrianus J.; Abdurrachim, Desiree; van Nierop, Bastiaan J.; Koeman, Anneke; van der Kroon, Inge; Baartscheer, Antonius; Schumacher, Cees A.; Strijkers, Gustav J.; Houten, Sander M.; Zuurbier, Coert J.; Nicolay, Klaas; Prompers, Jeanine J.
<x xml:space="preserve">Abstract</x> 31P MRS provides a unique non‐invasive window into myocardial energy homeostasis. Mouse models of cardiac disease are widely used in preclinical studies, but the application of 31P MRS in the in vivo mouse heart has been limited. The small‐sized, fast‐beating mouse heart imposes challenges regarding localized signal acquisition devoid of contamination with signal originating from surrounding tissues. Here, we report the implementation and validation of three‐dimensional image‐selected in vivo spectroscopy (3D ISIS) for localized 31P MRS of the in vivo mouse heart at 9.4 T. Cardiac 31P MR spectra were acquired in vivo in healthy mice (n = 9) and in transverse aortic constricted (TAC) mice (n = 8) using respiratory‐gated, cardiac‐triggered 3D ISIS. Localization and potential signal contamination were assessed with 31P MRS experiments in the anterior myocardial wall, liver, skeletal muscle and blood. For healthy hearts, results were validated against ex vivo biochemical assays. Effects of isoflurane anesthesia were assessed by measuring in vivo hemodynamics and blood gases. The myocardial energy status, assessed via the phosphocreatine (PCr) to adenosine 5′‐triphosphate (ATP) ratio, was approximately 25% lower in TAC mice compared with controls (0.76 ± 0.13 versus 1.00 ± 0.15; P < 0.01). Localization with one‐dimensional (1D) ISIS resulted in two‐fold higher PCr/ATP ratios than measured with 3D ISIS, because of the high PCr levels of chest skeletal muscle that contaminate the 1D ISIS measurements. Ex vivo determinations of the myocardial PCr/ATP ratio (0.94 ± 0.24; n = 8) confirmed the in vivo observations in control mice. Heart rate (497 ± 76 beats/min), mean arterial pressure (90 ± 3.3 mmHg) and blood oxygen saturation (96.2 ± 0.6%) during the experimental conditions of in vivo31P MRS were within the normal physiological range. Our results show that respiratory‐gated, cardiac‐triggered 3D ISIS allows for non‐invasive assessments of in vivo mouse myocardial energy homeostasis with 31P MRS under physiological conditions. Copyright © 2015 John Wiley & Sons, Ltd.